2019
DOI: 10.1016/j.ejvs.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Aortic and Systemic Arterial Stiffness Responses to Acute Exercise in Patients With Small Abdominal Aortic Aneurysms

Abstract: WHAT THIS PAPER ADDS Elevated arterial stiffness is associated with aneurysm progression and probably contributes to the high cardiovascular risk of patients with abdominal aortic aneurysms (AAA). It is demonstrated herein that the changes in aortic and systemic arterial stiffness are lower in patients with AAA after exercise compared with seated rest. This effect was most marked following higher intensity interval exercise. This attenuation in arterial stiffness suggests there may be an acute cardiovascular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
(60 reference statements)
1
14
1
Order By: Relevance
“…Vascular stiffness is increased in patients with AAA compared to healthy adults of a similar age. This finding is concordant with data arising from studies involving similarly aged aneurysm patients [30,31]. AAA confers a cardiovascular comorbidity burden prior to surgical intervention and a higher risk of adverse cardiovascular events in the 5 years following elective surgery [32].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Vascular stiffness is increased in patients with AAA compared to healthy adults of a similar age. This finding is concordant with data arising from studies involving similarly aged aneurysm patients [30,31]. AAA confers a cardiovascular comorbidity burden prior to surgical intervention and a higher risk of adverse cardiovascular events in the 5 years following elective surgery [32].…”
Section: Discussionsupporting
confidence: 88%
“…Vascular stiffness, heart rate and central blood pressure indices were assessed by two operators at baseline, week 3 and week 12 using the SphygmoCor Xcel (SphygmoCor ver 6.31, AtCor Medical Pty. Ltd., Sydney, Australia) and a previously described protocol [30]. RDW was measured in whole blood as part of full blood count analyses.…”
Section: Methodsmentioning
confidence: 99%
“…A recent large retrospective study reported a mean reduction of 13.6 ml kg −1 min −1 [95% confidence interval (CI) 12.0−15.2, P < 0.001] in VO 2 peak in people with AAA (n = 124) compared with apparently healthy age-matched individuals (n = 108) (Rose et al, 2018). In support of this finding, a recent comparative study reported that people with a small AAA (<5.5 cm) demonstrate significantly lower cardiorespiratory fitness (n = 22, VO 2 peak 19.0 ± 3.5 ml kg −1 min −1 ) when compared with those without an AAA (n = 22, VO 2 peak 24.5 ± 2.8 ml kg −1 min −1 , P ≤ 0.001) (Perissiou et al, 2019).…”
Section: Cardiorespiratory Fitness In People With Aaamentioning
confidence: 63%
“…A recent large retrospective study reported a mean reduction of 13.6 ml kg −1 min −1 [95% confidence interval (CI) 12.0−15.2, P < 0.001] in trueV̇normalO2peak${\dot V_{{{\rm{O}}_{\rm{2}}}{\rm{peak}}}}$ in people with AAA ( n = 124) compared with apparently healthy age‐matched individuals ( n = 108) (Rose et al., 2018). In support of this finding, a recent comparative study reported that people with a small AAA (<5.5 cm) demonstrate significantly lower cardiorespiratory fitness ( n = 22, trueV̇normalO2peak${\dot V_{{{\rm{O}}_{\rm{2}}}{\rm{peak}}}}$ 19.0 ± 3.5 ml kg −1 min −1 ) when compared with those without an AAA ( n = 22, trueV̇normalO2peak${\dot V_{{{\rm{O}}_{\rm{2}}}{\rm{peak}}}}$ 24.5 ± 2.8 ml kg −1 min −1 , P ≤ 0.001) (Perissiou et al., 2019). These findings from comparative studies suggest there is at least a ∼25% deficit in cardiorespiratory fitness in people with AAA.…”
Section: The Impact Of Abdominal Aortic Aneurysm On Cardiorespiratory...mentioning
confidence: 99%
See 1 more Smart Citation